2016
DOI: 10.1162/jocn_a_00999
|View full text |Cite
|
Sign up to set email alerts
|

Neural and Behavioral Evidence for Infants' Sensitivity to the Trustworthiness of Faces

Abstract: Face evaluation is a key aspect of face processing in humans, serving important functions in regulating social interactions. Adults and preschool children readily evaluate faces with respect to a person's trustworthiness and dominance. However, it is unclear whether face evaluation is mainly a product of extensive learning or a foundational building block of face perception already during infancy. We examined infants' sensitivity to facial signs of trustworthiness (Experiment 1) and dominance (Experiment 2) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
109
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(118 citation statements)
references
References 46 publications
9
109
0
Order By: Relevance
“…This finding replicates earlier evidence that, in adults, facial cues to trustworthiness that yield to more extreme trustworthiness judgments (i.e., very trustworthy or very untrustworthy) are easier to discriminate than those yielding to less extreme judgments, independently of their valence (i.e., whether the face is very trustworthy or very untrustworthy; Baccolo & Macchi Cassia, 2019). Accordingly, neuroimaging studies with adults reported a similar valence-independent sensitivity of the amygdala to trustworthiness cues (Said, Baron, & Todorov, 2009;Said, Dotsch, & Todorov, 2010), and electrophysiological studies with infants reported neural discrimination between neutral faces and both very trustworthy (+3 SD) and very untrustworthy (À3 SD) faces, but not between trustworthy and untrustworthy faces (Jessen & Grossmann, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding replicates earlier evidence that, in adults, facial cues to trustworthiness that yield to more extreme trustworthiness judgments (i.e., very trustworthy or very untrustworthy) are easier to discriminate than those yielding to less extreme judgments, independently of their valence (i.e., whether the face is very trustworthy or very untrustworthy; Baccolo & Macchi Cassia, 2019). Accordingly, neuroimaging studies with adults reported a similar valence-independent sensitivity of the amygdala to trustworthiness cues (Said, Baron, & Todorov, 2009;Said, Dotsch, & Todorov, 2010), and electrophysiological studies with infants reported neural discrimination between neutral faces and both very trustworthy (+3 SD) and very untrustworthy (À3 SD) faces, but not between trustworthy and untrustworthy faces (Jessen & Grossmann, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with this hypothesis, two recent studies by Grossmann (2016, 2017) suggest that even preverbal infants are sensitive to the face information that, in older children and adults, convey trust perception. In these studies, 7-months-old infants showed neural discrimination between neutral faces and those rated high or low on trustworthiness (Jessen & Grossmann, 2016), even when faces were presented subliminally (Jessen & Grossmann, 2017). Moreover, infants preferentially oriented their attention toward faces judged as trustworthy by adults rather than those judged as untrustworthy.…”
mentioning
confidence: 98%
“…There is only a single study assessing infants' responses to more human-specific aspects of powerful appearance (Jessen and Grossmann 2016). As an indication of infants' sensitivity to variation in facial structure, 7-month-olds prefer to look at faces that adults judge as "trustworthy" relative to faces that adults judge as "untrustworthy".…”
Section: Infants' Earliest Understanding Of the Physical Manifestatiomentioning
confidence: 99%
“…There is only a single study assessing infants' responses to more human-specific aspects of powerful appearance (Jessen & Grossmann, 2016). As an indication of infants' sensitivity to variation in facial structure, 7-month-olds prefer to look at faces that adults judge as "trustworthy" relative to faces that adults judge as "untrustworthy".…”
Section: Infants' Earliest Understanding Of the Physical Manifestatiomentioning
confidence: 99%